A nationwide investigation of CPR courses, books, and skill retention. (January 2019) - Jensen, Theo Walther; Møller, Thea Palsgaard; Viereck, Søren; Roland Hansen, Jens; Pedersen, Thomas Egesborg; Ersbøll, Annette Kjær; Lassen, Jens Flensted; Folke, Fredrik; Østergaard, Doris; Lippert, Freddy
Abstract: Introduction: Survival from Out-of-Hospital Cardiac Arrest is highly associated with bystander cardiopulmonary resuscitation. The quality of bystander CPR is influenced by citizens attending Basic Life Support (BLS) courses and the quality of these courses. The purpose of the study was to investigate content, quality and compliance with the European Resuscitation Council (ERC) guidelines in national Danish BLS courses and the skill retention. Methods: Books from 16 different course providers were analyzed for compliance with guidelines using the principle of mutually exclusive and collectively exhaustive questioning. Observation of 56 BLS courses were conducted using an evaluation sheet, with a five-point Likert scale including theoretical, technical, and non-technical skills. BLS skills of participants were assessed with a follow-up test 4–6 months after a course using a modified Cardiff Test. Results: Analysis of the books, showed compliance with ERC guidelines of 69% on the examined items. Courses using ERC educational structure and having maximum six participants per instructor were associated with high quality in the course observations and a better follow-up test. Especially, the use of automated external defibrillator showed significant odds ratio (OR) of 21.8 (95% CI 4.1–114.7) to 31.3 (95% CI 3.7–265.1) of achieving high quality on courses with similar results in the follow-up test. Conclusion: National BLS courses had significant variation in the content of books, and compliance to ERC guidelines during courses and in skills retention 4–6 months after the courses. This study can be used to further improve and standardize BLS courses.